Determine Type and Concentration of Active Ingrediants For Some Local Plants by using Technique High Performance Liquid Cromotography (HPLC) - Ayyub j.Abdlrahmaan Al-bayaty (Tikrit Journal of Pure Science, 2023)
Plants of Plantago, Silybum marinum and Achilla located from several regions of Governorates (Sulaimania, Diala, Salah-deen and Kurkuk) in order determine type and concentration Active Ingrediants For this plants by using HPLC echnique.The plants dried on the shade and 5gm of each plants taken and put in plastic can for analysin.The analysis made in the chemical Laboratores of ministry Science and Technology which showed plantago plant contain the following compounds: Salysilic acid, kaempferol, Gentisic Vanilic acid, Chlorogentic acid, Coumaric acid, ferulicacid andAucubin by 34.93%,4.55%,2.72%,1.67%,0.70%,8.59%,21.42% and9.12% while contain compounds: Silychrstin A, Silychrstin B, Silybins A, Isosilybin s A, Silydianin, Silybins by42.24%,14.89%,30.23%,3.30%,2.74%,4.86% and1.71% B. And plnat Achillea contain: Camphen,) Terpinine (α and ϒ), borneol, phellandrene-01, Terpihen-4-01, Terpeenin, terpinol, Piperitone and Cinol 8-1by 4.31%, 3.35%, 24.43%,7.73%,24.88%,7.56%,7.13%,12.8% and7.77%.